(untitled) (Applied Biological Research, 2020)
The purpose of this study was to highlight the determinants of abdominal obesity among Punjabi adult males. A total of 102 volunteer male subjects (40-60 yr) belonging to a group of people who regularly visited the Punjab Agricultural University campus, Ludhiana (India) for either morning or evening walk were enrolled for a study to identify dominant factors associated with abdominal obesity (AO) among the subjects. The subjects were divided into three groups as per their AO grade. The anthropometric parameters, food intake, physical activity and substance use were recorded using standardized procedures. All the anthropometric parameters of the studied group were higher than the reference values. The daily protein intake of subjects with grade II AO was significantly (p ≤ 0.001) lower than the subjects with either no AO or grade I AO. The maximum number of subjects as regular alcohol drinkers was highest in grade II of AO. Physical activity like walking, jogging etc. was more prevalent in groups with lower abdominal obesity. Physical activities were inversely and significantly (p ≤ 0.01, 0.05) correlated with body weight and BMI. Animal protein to plant protein ratio had a positive and significant (p ≤ 0.10, 0.05) relationship with body weight and BMI. The results concluded that the waist hip ratio, waist height ratio, conicity index and abdominal volume index are more reliable parameters for determining abdominal obesity and physical activity is more prominent determinant of abdominal obesity in comparison to dietary factors.